Prevalence and Patterns of Physical Activity amongst Students of Ameeruddin Medical College, Lahore - Rozina Shahadat Khan; Sarah Khalid; Nabeel Athar; Ayesha Saleem; Laiba Saeed; Tahreem Sana (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College)
Objective: To determine the low, moderate, and high-levels of physical activity based on total metabolic equivalent task (MET)- minutes per week of physical activity in relation to gender, accommodation, and academic year of medical school amongst students of a medical college. Methods: This cross-sectional study includes 177 medical undergraduate students, selected through simple random sampling from December 2023 to March 2024. A scoring system was developed according to the International Physical Activity Questionnaire scoring system categorizing levels of physical activity as low, moderate, and high based on MET-minutes calculated for walking, moderate, and vigorous activities. To find relation of different levels of physical activity with age, gender, accommodation and education, the chi square test of significance was utilized. The p-value < 0.05 was considered statistically significant. Results: Total weekly MET-minutes calculated by combining the MET-minutes of walking, moderate, nd vigorous activities was less than 600 for 55 (31.1%) students categorized as low level of physical activity. Among the students, 77 (43.5%) had a total MET-minutes/week score between 600 and 3000, indicating a moderate level of physical activity. Meanwhile, 45 students (25.4%) had a score exceeding 3000, categorized as a high level of physical activity. Overall, the majority (43.5%) engaged in moderate physical activity in their daily lives, while 25.4% performed high levels of activity, and 31.1% engaged in low levels of physical activity. No significant relation of different levels of physical activity with age, gender accommodation and education were found. Conclusion: Females exhibited lower levels of high-level activity compared to males. Both hostel residents and day scholars showed an improvement in moderate physical activity levels but a decline in vigorous activity levels. The overall high prevalence of physical inactivity especially amongst female residents of hostel or day scholars demands more awareness programs and mandatory extracurricular physical activities. Future research should be focused on determinants of physical inactivity amongst medical students.